2016
DOI: 10.1016/j.parkreldis.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant Parkinson's disease caused by SNCA duplications

Abstract: The discovery in 1997 that mutations in the SNCA gene cause Parkinson’s disease (PD) greatly advanced our understanding of this illness. There are pathogenic missense mutations and multiplication mutations in SNCA. Thus, not only a mutant protein, but also an increased dose of wild-type protein can produce autosomal dominant parkinsonism. We review the literature on SNCA duplications and focus on pathologically-confirmed cases. We also report a newly-identified American family with SNCA duplication whose proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
145
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 28 publications
4
145
0
1
Order By: Relevance
“… a Marras et al , 2011; b Alcalay et al , 2013; c Somme et al , 2015; d Ehrminger et al , 2015; e Kertelge et al , 2010; f Alcalay et al , 2014; g Sixel-Doring et al , 2015; h Simon-Tov et al , 2015; i Alcalay et al , 2012; j Neumann et al , 2009; k Gan-Or et al , 2015; l Konno et al , 2016; m Petrucci et al , 2016; n Nishioka et al , 2009.…”
Section: Neurobiology Underlying Visual Changes: Genetic Basis For Hementioning
confidence: 99%
“… a Marras et al , 2011; b Alcalay et al , 2013; c Somme et al , 2015; d Ehrminger et al , 2015; e Kertelge et al , 2010; f Alcalay et al , 2014; g Sixel-Doring et al , 2015; h Simon-Tov et al , 2015; i Alcalay et al , 2012; j Neumann et al , 2009; k Gan-Or et al , 2015; l Konno et al , 2016; m Petrucci et al , 2016; n Nishioka et al , 2009.…”
Section: Neurobiology Underlying Visual Changes: Genetic Basis For Hementioning
confidence: 99%
“…Most PD cases are sporadic and of unknown etiology, although during the last years the identification of gene mutations responsible for familial forms of PD and the mapping of risk variants for the disease [4] have improved our understanding of the disease. One of the first mutated gene that was found to be associated with familial PD was α-synuclein [5,6] and additional missense mutations and duplications have been found to be rare causes of hereditary PD or PD-like syndromes [7][8][9][10]. Moreover, genome-wide association studies have demonstrated an association between non-coding variants in and around the α-synuclein gene and sporadic disease [11].…”
Section: Parkinson's Disease Molecular Hallmarksmentioning
confidence: 99%
“…PD families with members carrying four copies of SNCA gene have been detected in South Africa, Iran, Japan, Pakistan and Italy [35][36][37][38][39][40]: in general, triplication generates very high expression of mRNA and protein and influences the clinical manifestations of PD, causing severe forms of Parkinsonism similar to dementia with Lewy body. Duplications have been reported in more numerous families than triplications [33,38,[41][42][43][44][45][46][47][48][49][50][51]. In some of the patients with the same ethnic background (Japan), haplotype analysis revealed their derivation from common founders [43,44].…”
Section: Sncamentioning
confidence: 99%